Shame, Culture, and American Criminal Law - Massaro, Toni M. (1991)
The purpose of this Article is to analyze whether this link is one that American criminal court judges can, or should, exploit. I begin with a description of the new shaming sanctions and the possible justifications for this type of penalty. I then identify both psychological and anthropological aspects of the phenomenon of shame, or losing face. I describe several cultures in which shaming practices are, or were, significant means of sanctioning behavior, and outline the shared features of these cultures. These psychological and anthropological materials, taken together, suggest that shaming practices are most effective and meaningful when five conditions are satisfied. First, the potential offenders must be members of an identifiable group, such as a close-knit religious or ethnic community. Second, the legal sanctions must actually compromise potential offenders' group social standing. That is, the affected group must concur with the legal decisionmaker's estimation of what is, or should be, humiliating to group members. Third, the shaming must be communicated to the group and the group must withdraw from the offender - shun her - physically, emotionally, financially, or otherwise. Fourth, the shamed person must fear withdrawal by the group. Finally, the shamed person must be afforded some means of regaining community esteem, unless the misdeed is so grave that the offender must be permanently exiled or demoted